2023
DOI: 10.1021/acs.est.3c02815
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics Enhance the Prevalence of Antibiotic Resistance Genes in Anaerobic Sludge Digestion by Enriching Antibiotic-Resistant Bacteria in Surface Biofilm and Facilitating the Vertical and Horizontal Gene Transfer

Tianyi Luo,
Xiaohu Dai,
Wei Wei
et al.

Abstract: Antibiotic resistance genes (ARGs) and microplastics (MPs) are recognized as emerging contaminants and threats to global human health. Despite both of them being significantly detected in their "hotspots", i.e., waste activated sludge (WAS), rare studies on how MPs affect ARGs and antibioticresistant bacteria (ARB) in anaerobic sludge digestion are available. Herein, the fate of ARGs and ARB after exposure to MPs of three dosages (10, 30, and 80 particles/g-TS), three polymer types (LDPE, PET, and PS), and thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Four books, all addressing waste technologies, were identified and excluded. Finally, articles out of the scope of this work (i.e., not addressing e-waste microplastics) were excluded (n = 5), namely, microplastics from glass recycling [26], found in marine fish species [27], contributing to antibiotic resistance in sludge [28], on international agreements [29], and on 3D printer waste (as it addressed microplastics generated in the activity and not those directly from electronics) [30]. A total of 24 research articles were reviewed, comprising all available original literature at the time.…”
Section: Methodsmentioning
confidence: 99%
“…Four books, all addressing waste technologies, were identified and excluded. Finally, articles out of the scope of this work (i.e., not addressing e-waste microplastics) were excluded (n = 5), namely, microplastics from glass recycling [26], found in marine fish species [27], contributing to antibiotic resistance in sludge [28], on international agreements [29], and on 3D printer waste (as it addressed microplastics generated in the activity and not those directly from electronics) [30]. A total of 24 research articles were reviewed, comprising all available original literature at the time.…”
Section: Methodsmentioning
confidence: 99%
“…And during the aging process, biofilms are formed on the surface of MPs, and the formation of biofilms will indirectly change the roughness, surface charge, and surface free energy of MPs, thus affecting the interaction between MPs and ATs [174]. Although it has been found that the bacterial organisms present in the biofilm formed on the surface of MPs have a certain degradation effect on ATs [175], the degradation effect is poor and the degradation period is long compared to its adsorption, such that the bacterial degradation in the biofilm is negligible [176]. In summary, MPs undergoing the aging process-resulting in increased surface areas, increased adsorption sites, the production of oxygen (increased polarity), oxygen-containing functional groups, biofilms, and fouling-will also increase the charge, roughness, and porosity, and will accumulate greater concentrations of ATs or other contaminants [177].…”
Section: Aging Behaviorsmentioning
confidence: 99%
“…There is clear evidence that increased levels of ARGs are linked to human activities globally, including in aquaculture (Reverter et al., 2020) and in agriculture (Knapp et al., 2010; Zheng et al., 2022), where the application of manure, fertilizers, biosolids, sludge, and wastewater can lead to this increase. In addition to the primary cause—the widespread use and even abuse of antibiotics—multiple other human‐caused factors also can affect the spread and evolution of ARGs, with many of them contributing to the proliferation of ARGs; for example, pollution with heavy metals (Yi et al., 2022), microplastics (Luo et al., 2023; Zhu et al., 2022), artificial sweeteners (Yang et al., 2023), and climate change (Burnham, 2021; Li et al., 2022; Reverter et al., 2020). High levels of ARGs caused by the use of antibiotics on humans and animals can also be delivered to the environment.…”
Section: Link To Human Activitymentioning
confidence: 99%